H Syndrome: A Rare Genodermatosis Imaged With 18F-FDG PET/CT. (January 2018) - Turpin, Sophie; Patey, Natalie; Beaudin, Marianne; Mitchell, Grant; Lambert, Raymond
Abstract : Abstract: H syndrome (OMIM 612391) is an extremely rare autosomal recessive genodermatosis, characterized by extensive skin infiltration. We report a case imaged with 18 F-FDG PET/CT.